Interventions designed to increase scholarly activity and achieve promotion among primarily junior clinical faculty in the United States: a scoping review - Heather A. Billings; Ashlee Mills Duffy; Gary L. Beck Dallaghan; Emily J. Glenn; Eric S. Peeples; Matthew R. Sandbulte; Jason F. Shiffermiller; Carrie Valenta; Bethany R. Lowndes; Jana L. Wardian (BMC Medical Education)
Abstract Background For many U.S. academic physicians, direct patient care is the primary focus of daily work and the most important professional responsibility. Concurrently, some degree of scholarly activity is often required for career advancement. Junior clinical faculty often face challenges that limit their success in this area such as heavy clinical workloads or other time constraints, a lack of personal expertise or experience, mentorship, and institutional infrastructure. Support systems and faculty development interventions may mitigate these challenges and contribute to increased academic productivity and promotion. The objective of this study was to perform a scoping review of literature on strategies which increase scholarly activity among junior clinical faculty in the United States to determine the extent to which this topic has been scientifically investigated, the form of the employed strategies for supporting junior clinical faculty scholarly activity, the types of scholarly activity measured, and the research methods used. Methods An online search of PubMed, CINAHL, Cochrane Library, Embase, ERIC and APA PsycINFO databases was conducted and supplemented by a manual search of references and citations. Articles published between January 1, 2012, and February 7, 2025, that described faculty development interventions designed to increase scholarly productivity of junior clinical faculty in the United States were included. We employed a structured data extraction algorithm, extracted data in dyads, and resolved any inconsistencies using a third extractor. Included publications were categorized by the primary intervention strategy they employed. Results Eighteen publications are included in this scoping review. The most common primary strategies for supporting scholarly activity were peer-mentoring (5/18, 28%) and traditional mentoring (5/18, 28%). Other strategies included grants and funding (4/18, 22%), faculty development and training (2/18, 11%), and protected time (1/18, 6%). Two of the 18 publications included a control group. Conclusions Mentoring was the most common strategy to support scholarly activity of junior clinical faculty followed by faculty development programs. Scholarly activity is often measured by publications, grant funding, and presentations. A major gap in the current literature is the absence of any high-quality research demonstrating a beneficial effect on the scholarly activity of junior clinical faculty.